Demographic and clinical characteristics of patients involuntarily hospitalized in an Italian psychiatric ward: a 1-year retrospective analysis: Characteristics of patients involuntarily hospitalized in an Italian psychiatric ward - Di Lorenzo, Rosaria; Vecchi, Laura; Artoni, Cecilia; Mongelli, Francesca; Ferri, Paola (Acta Biomedica Atenei Parmensis, 2018)
Background: In Italy, psychiatric compulsory treatments are regulated by Law 180 of 13-5-1978 that establishes three criteria: 1) acute psychiatric conditions requiring urgent treatment, 2) patient’s refusal of treatment, 3) inpatient treatment is necessary and cannot be postponed. Aim: To highlight demographic and clinical risk factors for involuntary treatments. Methods: We retrospectively collected all hospitalizations in the Service of Psychiatric Diagnosis and Treatment of a northern Italian town from 1-1-2015 to 31-12-2015. We statistically compared demographic and clinical variables related to voluntarily and involuntarily admitted patients and their hospitalizations. Results: We divided our sample into patients voluntarily hospitalized (PVH=236) and involuntarily (PIH=160) according to their voluntary (VH= 304) and involuntary (IH=197) hospitalizations. PIH were older than PVH and, more frequently, lived alone and were unemployed (p<0.001). “Acute worsening of psychopathology” for IH and “Suicidality” for VH were the prevalent reasons (p<0.001). IH was longer than VH (p<0.001). Among PIH, the most frequent diagnoses were “Schizophrenia and Other Psychosis” (ICD-9-CM) and “Ineffective Impulse Control + Disturbed Personal Identity” (NANDA-I) (p<0.001). During hospitalizations, PIH more often than PVH presented aggressive behavior (p<0.001). At discharge, PIH were more frequently sent to another psychiatric ward or protected facility with long-acting injectable antipsychotics (p<0.001). Conclusions: Our involuntarily admitted patients were affected by severe psychiatric disorders with social maladjustment and required complex therapeutic and rehabilitative programs to counteract aggressive behaviour, poor therapeutic compliance and prolonged hospitalizations. The assessment of patients’ characteristics can help clinicians recognize who are at risk for compulsory treatment and prevent it.